THE EFFECT OF NEUROMUSCULAR ELECTRICAL STIMULATION (NMES) AND PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION (PNF) IN INCREASING EXTREMITY MUSCLE STRENGTH OF HEMIPARESIS DEXTRA PATIENT: A CASE STUDY - Chodijah, Siti; Herawati, Isnaini (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Stroke is the second leading cause of death and third disability in the world. Data from the World Stroke Organization shows that every year there are 13.7 million new cases of stroke and about 6.7 million deaths that occur due to stroke. Stroke causes paralysis that worsens, and creates limitations in contractile or non-contractile tissue, and reduces range of motion in joints. Case Presentation: A case study on a 68-year-old man who had his first stroke in August 2020 and found a decrease in muscle strength, pain at the end of movements of shoulder, elbow and knee flexion along with decreased functional ability in the right extremity. Management and outcome: The patient received a therapeutic approach with NMES and PNF for 4 times for 2 weeks. This programs could improve muscle strength and decreased the level of pain among men with Hemiparesis Dextra Discussion: The study states that NMES appears to be an effective physical rehabilitation treatment to initiate skeletal muscle anabolic processes that promote muscle growth and strengthening in hemiparetic and healthy older skeletal muscle. In addition, PNF technique to the non-affected side as well as the affected side, where both had abnormally increased muscle tone and stiffness due to a post-stroke upper motor neuron lesion, had positive effects. Furthermore, the PNF combined pattern is an effective treatment method for increasing the muscle activity. Conclusion: After physiotherapy treatment 4 times for 2 weeks there was an increase in muscle strength and a decrease in pain at the end of passive flexion of the shoulder, elbow and knee.